Efficacy, chemical composition, and pharmacological effects of herbal drugs derived from Fritillaria cirrhosa D. Don and Fritillaria thunbergii Miq. - Fan Wu; Mei Tian; Yuefeng Sun; Changhao Wu; Xue Liu (Frontiers Media S.A., 2022)
Fritillaria cirrhosa D. Don and F. thunbergii Miq. belong to the genus Fritillaria within the Liliaceae family. They are used in traditional Chinese medicines that are often administered in clinical settings as they have notable effects on cough, bronchitis, pneumonia, lung injury, cancer, and other diseases. In this review, we focus on the history, origin, similarities, and differences in efficacy, chemical composition, and pharmacological outcomes of the drugs obtained from F. cirrhosa (FRC) and F. thunbergii (FRT). We list various valuable pharmacological effects of FRC and FRT, including antitussive, expectorant, anti-inflammatory, antioxidant, and anticancer effects. Thus, this review offers a basis for the medical application of and further research into the pharmacological impacts of these two drugs. We believe that new drugs derived from the phytoconstituents of F. cirrhosa and F. thunbergii that have specific therapeutic properties can be developed in the future.